Estimating the strain-rate dependent parameters of Cowper-Symonds and Johnson-Cook material models by Taguchi arrays - Škrlec, Andrej (Strojniški vestnik, 2016)
To reduce R&D cost the products behaviour i n exploitation is predicted using numerical simulations in early R&D phases. If a structure is subjected to a high - strain rate loading this effect should be considered in the material models that are used for numerical simulations. This article shows how t he strain - rate dependent material parameters can be determined by combining the experimental data with the numerical simulations. The presented methodology is based on an application of Taguchi arrays for finding the most adequate values for the strain - rat e dependent parameters. The presented methodology is applied on the practical case, for which the parameters of the Cowper - Symonds and Johnson - Cook material models are estimated.
Keywords: eksplicitna dinamika; finite element method; hitrost specifične deformacije; metoda končnih elementov; obnašanje materialov; Taguchi-jeve ortogonalne matrike